Densification of Firn on Langjökull Glacier, Iceland - Hulda Rós Helgadóttir 1991- (2015)
Langjökull is the second largest glacier in Iceland, around 925 square kilometers (Björnsson, 2009), and lies in the western higlands of the island. It is a temperate glacier like other glaciers in Iceland, which means that the temperature in the ice is at pressure melting point except for the uppermost meters where seasonal temperature changes from the surface are detectable. The ice tunnel is situated in the south-west part of Langjökull, north-east to Geitlandsjökull, and is placed close to the equilibrium line altitude at around 1270 m a.s.l. The tunnel gives a unique opportunity to explore the physical properties of glaciers in general, and the properties of Langjökull glacier. Density measurements were made along the tunnel to find out at what depth the firn becomes ice. Temperature measurements were made as well. All measurements were made on March 11th and April 12th 2015. Langjökull er næststærsti jökull landsins, um 925 ferkílómetrar (Björnsson, 2009) og liggur á vesturhálendi Íslands. Hann er þíðjökull eins og aðrir jöklar Íslands, en það merkir að hitastig í jöklinum er við þrýstingsbræðslumark nema í efstu metrunum þar sem veðurfarsbreytingar við yfirborð koma fram. Ísgöngin eru staðsett á suðvestur hluta Langjökls, rétt norðaustan Geitlandsjökuls. Göngin eru við jafnvægislínu í u.þ.b. 1270 hæð og gefa einstakt tækifæri til könnunar á eðliseiginleikum jökla almennt og Langjökuls. Mælingar voru gerðar á eðlismassa inn eftir göngunum til að komast að því á hvaða dýpi hjarn verður að jökulís. Einnig var hitastig hjarnsins mælt inn eftir göngunum. Mælingar á voru gerðar þann 11. mars og 12. apríl 2015.